PROCESSING OF A NIGERIAN COLUMBITE-RICH ILMENITE ORE FOR IMPROVED INDUSTRIAL APPLICATION BY SULPHURIC ACID SOLUTION - Alafara Abdullahi Baba; Sunday O. Jacob; Daud T. Olaoluwa; Abdulrahman Abubakar; Adeola O. Womiloju; Fausat T. Olasinde; Aishat Y. Abdulkareem (Puslitbang tekMIRA, 2018)
Due to increasing technological advancements, the demand for pure niobium products emanated from columbite ore processing has led to the wide array of its application in capacitors, nuclear uses, superconducting RF cavities, an electromagnetic radiation detector, medical devices, and aerospace among others. Therefore, this paper focuses on the kinetics of dissolution of a Nigerian Columbite mineral in sulphuric acid solution for improved industrial applications. The effects of acid concentration, reaction temperature and particle size on the ore dissolution rate were examined. Experimental results showed that the ore dissolution increases with increasing acid concentration and temperature and decreases with increasing particle size fraction. With 2 mol/L H2SO4 solution, 60.2% of the ore dissolved within 120 minutes using <90µm particle size at a temperature of 75°C with moderate stirring (300 rpm). The unleached products were analyzed and found to contain siliceous compounds applicable as industrial by-products. The calculated activation energy (Ea) deduced to be 30.3 kJ/mol supported the proposed diffusion reaction mechanism for the first order dissolution process with a collision factor of 0.12 per minute. Hence, the dissolution data obtained in this study is an indication of thermodynamic feasibility for Nigeria Columbite ore fitness in improving science and technology for economic growth and development.